Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material as well as preparation method and application thereof
Through Ce doping and CeO2 coating the modified nickel-rich layered oxide positive electrode material, the problem of poor structural stability of the material during the high delitting cycle is solved, and significant electrochemical performance improvement and cost reduction are achieved.
Patent Information
- Application Number
- CN202411848633.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The nickel-rich layered oxide positive electrode material has poor structural stability during the high delitting cycle, and is prone to lattice distortion, interface side reactions and thermal runaway, resulting in capacity attenuation and safety problems.
Ce doping and CeO2 coating are used to coordinately modify the nickel-rich layered oxide positive electrode material. Through Ce doping, the lattice structure is adjusted and oxygen binding force is enhanced. CeO2 coating provides external protection to reduce electrolyte erosion and side reactions.
It significantly improves the structural stability and cyclic stability of the material, improves the discharge specific capacity, Coulomb efficiency and cyclic stability, and shows excellent electrochemical performance. At the same time, the preparation process is simple and the cost is low, which is suitable for large-scale production.
Smart Images

Figure CN119742331A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and relates to a lithium-ion battery positive electrode material, and specifically to a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material, and a preparation method and application thereof. Background Art
[0002] As the global demand for new energy continues to grow, lithium-ion batteries, as efficient and environmentally friendly energy storage devices, are widely used in electric vehicles and mobile electronic devices. As a key component of lithium-ion batteries, the performance of positive electrode materials directly affects the energy density, cycle life and safety of the battery. Nickel-rich layered oxide positive electrode materials are considered to be an important development direction for the next generation of power batteries due to their high energy density, good cycle performance and moderate cost. However, during high lithium de-cycling processes, the structural stability is poor, and lattice distortion, interfacial side reactions and thermal runaway are prone to occur, ultimately leading to capacity decay and safety issues. These problems seriously restrict the practical application of nickel-rich layered oxides in high-performance lithium-ion batteries. Therefore, improving their cycle stability and thermal stability is one of the main challenges of current research, and ion doping and surface coating are currently the most effective methods to improve the electrochemical properties of materials.
[0003] The patent application document with publication number CN113258059A discloses a multi-modified lithium-ion battery positive electrode material and a preparation method thereof. In the synthesis process of the positive electrode material, a precursor is synthesized by introducing CeO2 into the liquid phase during the coprecipitation process. However, CeO2 is difficult to dissolve in alkaline solutions and is unevenly dispersed, making it difficult to introduce the precursor. The subsequent sintering process does not treat the positive electrode material, and the destructive effects of acid ions on the structure cannot be avoided.
[0004] The patent application document with publication number CN115663139A discloses a nickel-cobalt-manganese multi-element positive electrode material, its preparation method and application, and lithium-ion battery. However, due to its complicated process, the sintering process is divided into two sintering processes, and the sintering temperature is too high, the content of doped rare earth elements is higher, it has a greater consumption cost, and is relatively limited; the subsequent electrochemical performance has not been greatly improved, and there is no support from other electrochemical performances. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention discloses a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material and a preparation method and application thereof. The modified nickel-rich layered oxide positive electrode material contains the doping element Ce and is coated with CeO2 on the surface, which enhances its structural stability, and significantly improves its discharge specific capacity, coulombic efficiency and cycle stability, showing excellent electrochemical properties. At the same time, the preparation process of the modified nickel-rich layered oxide positive electrode material is simple, the cost is low, and it is easy to mass produce.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material comprises the following steps:
[0008] S1. Prepare a 2M mixed salt solution of nickel source, cobalt source and manganese source in a molar ratio of 8:1:1;
[0009] S2. In an inert gas atmosphere, slowly add the mixed salt solution, precipitant and complexing agent described in step S1 into a sealed co-precipitation reactor, adjust the initial conditions for co-precipitation reaction, and filter, wash and dry the preformed precipitate to obtain a brown nickel-rich layered oxide precursor;
[0010] S3, grinding the brown nickel-rich layered oxide precursor and 0.5%-1.5% molar mass ratio of cerium source until they are completely mixed;
[0011] S4, after the mixing in step S3 is uniform, add 3-5% molar mass ratio of excess lithium source and grind and mix uniformly;
[0012] S5. Place the product obtained in step S4 in a tubular furnace for sintering. The sintering conditions are: first heat to 450-550°C at a heating rate of 2-4°C / min and keep warm for 8-9 hours, then continue to heat to 760-800°C and keep warm for 12-15 hours. After cooling to room temperature, grind and sieve to obtain Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material.
[0013] Furthermore, the nickel source used in step S1 is nickel sulfate, nickel nitrate, or nickel oxalate; the cobalt source is cobalt sulfate, cobalt nitrate, or cobalt oxalate; and the manganese source is manganese sulfate, manganese nitrate, or manganese oxalate.
[0014] Furthermore, the initial conditions of step S2 are adjusted as follows: the pH value is controlled at 11.45-11.5, the stirring speed is 400 r / min, and the reaction temperature is 55° C.; the preformed precipitate is washed with water until the pH is neutral and then dried.
[0015] Furthermore, in step S3, the cerium source is one of nano-scale cerium acetate, cerium sulfate, cerium hydroxide and cerium oxide.
[0016] Furthermore, in step S4, the lithium source is lithium hydroxide or lithium carbonate powder, and the ball mill frequency is set to 180 r / min.
[0017] Furthermore, in step S1, the precipitant is 4M sodium hydroxide, sodium carbonate, sodium oxalate, and the complexing agent is 4M ammonia water.
[0018] A Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material obtained by a method for preparing a nickel-rich layered oxide positive electrode material.
[0019] Disclosed is the application of a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material in lithium-ion batteries.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The modified nickel-rich layered oxide positive electrode material provided by the present invention contains the doping element Ce, and the surface of the modified nickel-rich layered oxide positive electrode material is coated with CeO2, the Ce doping content of the modified nickel-rich layered oxide positive electrode material is between 0.5% and 1.5%, and the (003) diffraction peak of the modified nickel-rich layered oxide positive electrode material XRD is shifted to the left, and has a larger lattice parameter; Ce doping mainly acts on the lattice structure of the material, and suppresses volume expansion and irreversible phase change by adjusting the lattice parameters and enhancing the oxygen binding force, while CeO2 coating provides external protection, forms a stable surface structure, reduces the probability of electrolyte erosion and side reactions, and effectively improves the structural stability and cycle stability of the nickel-rich layered oxide positive electrode material.
[0022] Furthermore, the preparation method of the modified nickel-rich layered oxide positive electrode material provided by the present invention is simple, and the performance is significantly improved. Specifically, after the precursor preparation process, a water washing operation is performed to reduce the influence of sulfate anions on the structure; in the mixing step, the nickel-rich layered oxide precursor is used for a double mixing method, first mixing the cerium source, and then mixing with lithium, to ensure the uniformity of the Ce element in each part; in the sintering process, a one-step sintering method is used, and two temperatures are used for heat preservation, which effectively reduces the steps of the sintering process, and the heat preservation step strengthens the sintering driving force. The method is simple and easy to implement, low cost, and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD diagrams of nickel-rich layered oxide positive electrode materials prepared in Examples 1-3 and Comparative Example 1 of the present invention.
[0024] Figure 2This is the SEM image and corresponding EDS image of the nickel-rich layered oxide positive electrode material prepared in Comparative Example 1 of the present invention.
[0025] Figure 3 This is the SEM image and corresponding EDS image of the nickel-rich layered oxide positive electrode material prepared in Example 1 of the present invention.
[0026] Figure 4 The SEM image and corresponding EDS image of the nickel-rich layered oxide positive electrode material prepared in Example 2 of the present invention.
[0027] Figure 5 This is the SEM image and corresponding EDS image of the nickel-rich layered oxide positive electrode material prepared in Example 3 of the present invention.
[0028] Figure 6 XRD and EIS graphs of the nickel-rich layered oxide positive electrode materials prepared in Examples 1-3 and Comparative Example 1 of the present invention.
[0029] Figure 7 This is a diagram of the chemical formation performance of the nickel-rich layered oxide positive electrode materials prepared in Examples 1-3 of the present invention and Comparative Example 1.
[0030] Figure 8 This is a rate performance diagram of the nickel-rich layered oxide positive electrode materials prepared in Examples 1-3 of the present invention and Comparative Example 1.
[0031] Fig. 9 This is a cycle performance diagram of the nickel-rich layered oxide positive electrode material prepared in Examples 1-3 of the present invention and Comparative Example 1 at a 1C rate, wherein the test temperature is room temperature and the voltage range is 2.75-4.3V. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below with reference to specific embodiments, but is not intended to limit the present invention.
[0033] The first aspect of the present invention discloses a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material, wherein the modified nickel-rich layered oxide positive electrode material contains the doping element Ce, and the surface of the modified nickel-rich layered oxide positive electrode material is coated with CeO2.
[0034] The modified nickel-rich layered oxide positive electrode material has a larger lattice parameter and a left-shifted (003) diffraction peak obtained by XRD; wherein the lattice parameters obtained by XRD satisfy: 2.85nm≦a≦2.87nm, 14.18nm≦a≦14.20nm.
[0035] The XRD spectrum of the modified nickel-rich layered oxide positive electrode material shows a characteristic peak of CeO2 (111) between 28 and 29 at 2 Thera.
[0036] The second aspect of the present invention provides a method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material, comprising the following steps:
[0037] (1) using nickel source, cobalt source and manganese source as raw materials, preparing a mixed salt solution, a precipitant and a complexing agent mixed solution as a precipitant and a complexing agent;
[0038] (2) In a sealed co-precipitation reactor, the initial conditions are adjusted, and the mixed salt solution and the mixed solution are slowly added into the reactor under a nitrogen atmosphere to carry out a co-precipitation reaction, and the preformed precipitate is filtered, washed with water, and then dried to obtain a brown nickel-rich layered oxide precursor;
[0039] (3) manually grinding the nickel-rich layered oxide precursor and cerium sources of different molar mass ratios in an agate mortar until uniform; wherein the molar mass ratio of the cerium source is between 0.5% and 1.5%;
[0040] (4) After the mixture in step 3 is mixed evenly, 3-5% molar excess of lithium source is added respectively, mixed evenly in a ball mill, and then further mixed manually using an agate mortar;
[0041] (5) The product obtained in step 4 is placed in a tubular furnace for a sintering process, and after cooling to room temperature, it is ground and sieved to obtain the modified nickel-rich layered oxide positive electrode material.
[0042] In the present invention, the cerium source is first mixed with the precursor to make the step-by-step process more uniform. During the precursor sintering process, the sintering provides a greater reaction driving force.
[0043] The modified nickel-rich layered oxide positive electrode material provided by the present invention contains the doping element Ce, and the surface of the modified nickel-rich layered oxide positive electrode material is coated with CeO2, and the (003) diffraction peak of the modified nickel-rich layered oxide positive electrode material XRD is shifted to the left, and has a larger lattice parameter. Ce doping mainly acts on the lattice structure of the material, suppressing volume expansion and irreversible phase change by adjusting the lattice parameter and enhancing the oxygen binding force, while CeO2 coating provides external protection, forms a stable surface structure, reduces the probability of electrolyte erosion and side reactions, and effectively improves the structural stability and cycle stability of the nickel-rich layered oxide positive electrode material.
[0044] Furthermore, the preparation method of the modified nickel-rich layered oxide positive electrode material provided by the present invention is simple and has significantly improved performance. Specifically, after the precursor preparation process, a water washing operation is performed to reduce the influence of sulfate anions on the structure; in the mixing step, the nickel-rich layered oxide precursor is used for a double mixing method, first mixing the cerium source, and then mixing with lithium, to ensure the uniformity of the Ce element in each part.
[0045] Furthermore, a one-step sintering method is used in the sintering process, and two temperatures are used for heat preservation, which effectively reduces the steps of the sintering process, and the heat preservation step strengthens the sintering driving force.
[0046] Furthermore, the method is simple and easy to implement, has low cost, and is suitable for mass production.
[0047] Furthermore, when the cerium source is added in an amount according to a stoichiometric ratio of 0.05-0.15, the cathode material thus prepared has a large lattice parameter and a strong oxygen binding force to inhibit volume expansion and irreversible phase change, thereby inhibiting lithium-nickel mixing and improving the structural stability of the cathode material.
[0048] Furthermore, when the cerium source is added in a stoichiometric ratio of 0.05-0.15, the surface of the positive electrode material thus prepared has a suitable coating amount of CeO2, which can protect the internal structure of the positive electrode material and prevent it from being corroded by the electrolyte during the battery cycle, while not affecting the charge and discharge capacity of the lithium-ion battery and the insertion and extraction of lithium ions.
[0049] In the present invention, when the nickel-rich layered oxide precursor is controlled to prepare the nickel-rich layered oxide positive electrode material, when the amount of cerium source added is according to the stoichiometric ratio of 0.05-0.15, Ce can be doped into the bulk phase of the material, and a suitable coating amount of CeO2 is uniformly produced on the surface, thereby significantly improving the structural stability of the positive electrode material obtained thereby.
[0050] In the present invention, the nickel source used is nickel sulfate, the cobalt source is cobalt sulfate, and the manganese source is manganese sulfate. A 2M mixed salt solution is prepared at a molar ratio of Ni:Co:Mn=8:1:1; the precipitant and the complexing agent are sodium hydroxide and ammonia water respectively;
[0051] In the present invention, the coprecipitation reaction conditions are: pH value is 11.50±0.05, stirring speed is 400r / min, reaction temperature is 55°C; suction filtration and water washing step is performed until pH is neutral;
[0052] In the present invention, the cerium source is nano-cerium oxide, and the added amount is 0.05-0.15 according to the stoichiometric ratio.
[0053] In the present invention, the lithium source is lithium hydroxide powder.
[0054] In the present invention, the ball mill parameter conditions are as follows: the frequency is set to 14 Hz (180 r / min), and the ball milling is performed for more than 4 hours.
[0055] In the present invention, the sintering conditions include: under oxygen conditions, heating to 500° C. at a heating rate of 3° C. / min and keeping the temperature for 8 hours, and then continuing to heat to 760° C. and keeping the temperature for 15 hours.
[0056] The third aspect of the present invention provides a nickel-rich layered oxide precursor prepared by the above preparation method;
[0057] A fourth aspect of the present invention provides a nickel-rich layered oxide positive electrode material prepared by the above preparation method;
[0058] A fifth aspect of the present invention provides a lithium-ion battery, which comprises the above-mentioned nickel-rich layered oxide positive electrode material.
[0059] In the following examples, all raw materials are commercially available. Unless otherwise specified, the room temperature in the present invention refers to 25±2°C. In the following examples, the relevant parameters are obtained by testing using the following methods:
[0060] (1) Morphology test: obtained by Zeiss Gemini 300 scanning electron microscope test;
[0061] (2) XRD test: obtained by Rigaku D / max 2500pc X-ray diffractometer;
[0062] (3) Electrochemical test:
[0063] In the following examples, the electrochemical performance of the positive electrode material was tested using a 2032 button cell.
[0064] The specific preparation process of 2032 button battery is as follows:
[0065] Preparation of pole pieces: A mixed slurry of 80% positive electrode material, 10% N-methylpyrrolidone containing polyvinylidene fluoride and 10% conductive carbon black is evenly coated on aluminum foil, weighed and placed in a vacuum drying oven at 70°C for 12 hours, and then punched into positive pole pieces with a diameter of 12 mm and a thickness of 120 μm.
[0066] Battery assembly: In a German Braun glove box filled with argon gas with water and oxygen content less than 1ppm, the positive electrode, separator, negative electrode and electrolyte were assembled into a 2032 button cell and left to stand for 6 hours. The electrolyte was 1M, the volume ratio of LiPF6+EC, DEC and DMC was 1:1:1, and the metal lithium sheet was the counter electrode.
[0067] Electrochemical performance test:
[0068] In the following example, the electrochemical performance of 2032 button cells was tested using Shenzhen Xinwell CT-4008Tn-5V10mA-HWX battery testing system, and the 1C charge and discharge current density was 200mA / g.
[0069] Formation performance test: The charge and discharge voltage range is controlled to be 2.75 to 4.3V. At room temperature, the button cell is charged and discharged at 0.1C to evaluate the first discharge specific capacity of the positive electrode material.
[0070] Cycle performance test: The charge and discharge voltage range was controlled to be 2.75 to 4.3 V. At room temperature, the button cell was charged and discharged for 5 cycles at 0.1 C, and then charged and discharged for 200 cycles at 1 C to evaluate the capacity retention rate of the positive electrode material.
[0071] Rate performance test: The charge and discharge voltage range was controlled to be 2.75 to 4.3 V. At room temperature, the button cell was charged and discharged for 5 times at 0.1 C, then for 5 times at 0.2 C, 0.3 C, 0.5 C, 1 C and 2 C, and finally for 5 times at 0.1 C to evaluate the rate performance of the positive electrode material.
[0072] Example 1
[0073] (1) nickel sulfate, cobalt sulfate and manganese sulfate are used as raw materials, and a 2 mol / L mixed salt solution is prepared at a molar mass ratio of Ni:Co:Mn=8:1:1, and a mixed solution of 4 mol / L NaOH and 4 mol / L NH3·H2O is used as a precipitant and a complexing agent;
[0074] (2) In a sealed coprecipitation reactor, 3 L of 1 mol / L NH3·H2O bottom solution was injected to adjust the pH value to 11.50±0.05, the reaction temperature was controlled at 55°C, the stirring speed was 400 r / min, and nitrogen was ventilated for 4 hours to exclude oxygen. The mixed salt solution and the mixed solution were slowly added to the reactor under a nitrogen atmosphere to carry out a coprecipitation reaction. The preformed precipitate was filtered, washed with water until the pH was neutral, and dried at 100°C for 24 hours to obtain a brown nickel-rich layered oxide precursor;
[0075] (3) manually grinding the nickel-rich layered oxide precursor and 0.5% molar mass ratio of nano-cerium oxide in an agate mortar until the powder is completely mixed with the brown precursor;
[0076] (4) After the mixture is evenly mixed in step 3, 5% molar excess of lithium hydroxide is added, and after mixing in a ball mill at 180 r / min for 4 hours, manual grinding is continued in an agate mortar for 30 minutes;
[0077] (5) placing the product obtained in step 4 in a tube furnace, heating it to 500° C. at a heating rate of 3° C. / min and keeping it at that temperature for 8 hours, then continuing to heat it to 760° C. and keeping it at that temperature for 15 hours, cooling it to room temperature, grinding it, and sieving it to obtain the modified nickel-rich layered oxide positive electrode material;
[0078] Example 2
[0079] According to the method of Example 1, except that the cerium source is doped with 1.0 mol% of nano-cerium oxide, and the rest is the same as Example 1, a nickel-rich layered oxide positive electrode material is prepared.
[0080] Example 3
[0081] According to the method of Example 1, except that the cerium source is doped with nano-cerium oxide at a molar weight ratio of 1.5%, and the rest is the same as Example 1, a nickel-rich layered oxide positive electrode material is prepared.
[0082] Example 4
[0083] (1) preparing a 2 M mixed salt solution of nickel nitrate: cobalt nitrate: manganese nitrate in a molar ratio of 8:1:1;
[0084] (2) Under a nitrogen atmosphere, the mixed salt solution described in step S1, 4M sodium carbonate and 4M ammonia water are slowly added to a sealed co-precipitation reactor, the initial conditions are adjusted to carry out a co-precipitation reaction, and the preformed precipitate is filtered, washed with water, and dried to obtain a brown nickel-rich layered oxide precursor; the pH value is controlled at 11.45-11.5, the stirring speed is 400r / min, and the reaction temperature is 55°C; the preformed precipitate is washed with water until the pH is neutral and then dried.
[0085] (3) grinding the brown nickel-rich layered oxide precursor and 0.75% by molar mass of nano-sized cerium hydroxide until they are completely mixed;
[0086] (4) After the mixing in step S3 is uniform, add 3% excess lithium carbonate powder by molar mass ratio, grind and mix uniformly;
[0087] (5) The product obtained in step S4 is placed in a tubular furnace for a sintering process. The sintering conditions are: firstly heating to 450°C at a heating rate of 2°C / min and keeping the temperature for 8.5 hours, then continuing to heat to 780°C and keeping the temperature for 12 hours, and then cooling to room temperature, grinding and sieving to obtain a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material.
[0088] Example 5
[0089] (1) preparing a 2 M mixed salt solution of nickel oxalate: cobalt oxalate: manganese oxalate in a molar ratio of 8:1:1;
[0090] (2) Under a nitrogen atmosphere, the mixed salt solution described in step S1, 4M sodium oxalate and 4M ammonia water are slowly added to a sealed co-precipitation reactor, the initial conditions are adjusted to carry out a co-precipitation reaction, and the preformed precipitate is filtered, washed with water, and dried to obtain a brown nickel-rich layered oxide precursor; the pH value is controlled at 11.45-11.5, the stirring speed is 400r / min, and the reaction temperature is 55°C; the preformed precipitate is washed with water until the pH is neutral and then dried.
[0091] (3) grinding the brown nickel-rich layered oxide precursor and 1.25% by molar mass of nano-sized cerium sulfate until they are completely mixed;
[0092] (4) After the mixing in step S3 is uniform, an excess amount of lithium carbonate powder with a molar mass ratio of 4% is added and ground and mixed uniformly;
[0093] (5) The product obtained in step S4 is placed in a tubular furnace for sintering. The sintering conditions are: first heating to 550°C at a heating rate of 4°C / min and keeping warm for 9 hours, then continuing to heat to 800°C and keeping warm for 13.5 hours. After cooling to room temperature, it is ground and sieved to obtain a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material.
[0094] Comparative Example
[0095] According to the method of Example 1, except that the cerium source addition part is skipped, the rest is the same as Example 1 to prepare a nickel-rich layered oxide positive electrode material.
[0096] The unit cell parameters of Examples 1-3 and Comparative Example are shown in Table 1.
[0097] Table 1
[0098]
[0099] It can be seen from Table 1 that, compared with the comparative example, Examples 1-3 exhibit larger lattice constants.
[0100] Further, such as Figure 1 (a) shows the X-ray diffraction images of Examples 1-3 and Comparative Example 1. As the Ce doping amount increases, the lattice spacing does not continue to increase, indicating that the doping amount has exceeded the solubility and the additional CeO2 tends to be enriched on the surface. The appearance of the CeO2 (111) characteristic peak further verifies this conclusion, indicating that the excess CeO2 not incorporated into the lattice gathers on the surface of the material to form a CeO2 coating layer. Figure 1The (003) main diffraction peak of Example 1-3 in (b) also shifts to the left, indicating that Ce is successfully doped into the nickel-rich layered oxide positive electrode material lattice. In addition, the overall intensity of the diffraction peak of the material is reduced, while the intensity of the CeO2 diffraction peak is increased, indicating the formation of the CeO2 coating layer and the influence of the change in Ce doping concentration on the material structure.
[0101] Further, such as Figure 2-5 The scanning electron microscope and energy spectrum images of the comparative example, Example 1, Example 2 and Example 3 prepared by the present invention are shown respectively. The results show that the doping modification does not change the spherical particle structure. The corresponding EDS images show that the surface of the nickel-rich layered oxide positive electrode material prepared in the example is loaded with a uniform distribution of Ce elements, indicating the formation of a uniform CeO2 coating layer.
[0102] Further, such as Figure 6 It is the EIS curve diagram of Example 1, Example 2, Example 3 and the comparative example. The intrinsic impedance of the nickel-rich layered oxide positive electrode material prepared in the example does not change significantly in the ultra-high frequency region, indicating that Ce doping and CeO2 coating do not affect the overall ohmic impedance of the battery, while the impedance value in the high frequency region is reduced, and when the proportion of the doped cerium source is 1%, it has the lowest interface transfer impedance. This is mainly due to the appearance of the uniform CeO2 coating layer. The ionic conductivity of the material is improved. When the CeO2 aggregation increases, it affects the deintercalation of Li, resulting in a slight increase in the interface transfer impedance; by comparing the low-frequency curves of Examples 1-3 and the comparative example, the nickel-rich layered oxide positive electrode materials prepared in the examples have good Li + The diffusion resistance is mainly due to the oxygen vacancies in the CeO2 coating on the surface that enhance the Li + The diffusion dynamics of the nanostructured carbon nanotubes contribute to the rate capability and interfacial stability during cycling.
[0103] Further, such as Figure 8 The figure is the performance diagram of Example 1, Example 2, Example 3 and the comparative example. Under the formation rate of 0.1C, compared with the comparative example, the modified materials all show higher first-cycle coulomb efficiency, and when the doping ratio is 1%, it has a first-cycle coulomb efficiency as high as 95.07%. This is because Ce 4+ The doping of CeO2 effectively enhances its lattice stability and structural stability during the cycle. The uniform CeO2 on the surface provides a good diffusion channel for lithium ions, which is manifested as a good first-cycle charge and discharge efficiency and good rate performance, such as Figure 7 shown.
[0104] Compared with the comparative example, Fig. 9As shown in the figure, when the doping ratio is 1%, the nickel-rich layered oxide positive electrode material prepared in the example shows excellent long-cycle performance, with a higher discharge specific capacity after 200 cycles at 1.0C rate, and a capacity retention rate of up to 83.52%, which is much higher than that of the comparative example (65.29%). This is mainly due to the stable Ce 4+ Doped and more uniform surface CeO2 coating layer. This combination of Ce doping and CeO2 coating not only provides structural stability inside the material, but also forms a stable protective layer on the surface of the material, achieving dual protection inside and outside, effectively improving the structural stability and cycle stability of nickel-rich layered oxide positive electrode materials.
[0105] The preferred embodiments of the present invention are described in detail above; however, the present invention is not limited thereto.
[0106] Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, including combining various technical features in any other suitable manner. These simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material, characterized in that: The following steps are involved: S1. Prepare a 2M mixed salt solution of nickel source, cobalt source and manganese source in a molar ratio of 8:1:1; S2. In an inert gas atmosphere, slowly add the mixed salt solution, precipitant and complexing agent described in step S1 into a sealed co-precipitation reactor, adjust the initial conditions for co-precipitation reaction, and filter, wash and dry the preformed precipitate to obtain a brown nickel-rich layered oxide precursor; S3, grinding the brown nickel-rich layered oxide precursor and 0.5%-1.5% molar mass ratio of cerium source until they are completely mixed; S4, after the mixing in step S3 is uniform, add 3-5% molar mass ratio of excess lithium source and grind and mix uniformly; S5. Place the product obtained in step S4 in a tubular furnace for sintering. The sintering conditions are: first heat to 450-550°C at a heating rate of 2-4°C / min and keep warm for 8-9 hours, then continue to heat to 760-800°C and keep warm for 12-15 hours. After cooling to room temperature, grind and sieve to obtain Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material.
2. The method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material according to claim 1, characterized in that: The nickel source used in step S1 is nickel sulfate, nickel nitrate, or nickel oxalate; the cobalt source is cobalt sulfate, cobalt nitrate, or cobalt oxalate; and the manganese source is manganese sulfate, manganese nitrate, or manganese oxalate.
3. The method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material according to claim 1, characterized in that: The initial conditions of step S2 are as follows: the pH value is controlled at 11.45-11.5, the stirring speed is 400 r / min, and the reaction temperature is 55° C.; the preformed precipitate is washed with water until the pH is neutral and then dried.
4. The method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material according to claim 1, characterized in that: The cerium source in step S3 is one of nano-scale cerium acetate, cerium sulfate, cerium hydroxide and cerium oxide.
5. The method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material according to claim 1, characterized in that: In step S4, the lithium source is lithium hydroxide or lithium carbonate powder, and the ball mill frequency is set to 180 r / min.
6. The method for preparing a Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material according to claim 1, characterized in that: In step S1, the precipitant is 4M sodium hydroxide, sodium carbonate, sodium oxalate, and the complexing agent is 4M ammonia water.
7. A Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material obtained by the preparation method described in any one of claims 1 to 6.
8. Use of the Ce-doped and CeO2-coated synergistically modified nickel-rich layered oxide positive electrode material as claimed in claim 7 in a lithium-ion battery.
Citation Information
Patent Citations
Rare earth element modified lithium ion battery positive electrode material and preparation method and application thereof
CN110911687A
Modified lithium nickel cobalt manganese oxide ternary positive electrode material and preparation method and application thereof
CN111320214A
Yttrium ion doped yttrium oxide coated and modified lithium-rich manganese-based positive electrode material, as well as preparation method and application
CN113422033A
Nano cerium oxide coated cerium-doped lithium-rich manganese-based positive electrode material and preparation method thereof
CN118315568A
Electrochemically active materials and methods of preparing the same
US20210193993A1
Cited By
Doping and coating integrated modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN120581559A